Почитание деревьев у татар севера Омской области - Galeeva, N. F.; Галеева, Н. Ф. (Издательство Тюменского государственного университета, 2016)
Since ancient times, animistic ideas (spiritualization of natural phenomena) have taken a special place in religious beliefs of the Siberian Tatars. Life of Siberians depended on their ability to survive in taiga and ability to use its gifts, that is why the cult of trees was one of the most important elements of the traditional religious system of this group of the Tatars. Echoes of the animistic beliefs still exist in our days. Culture and traditions of the Tatars from the north part of Omsk region also retain pre-Islamic remnants including the worship of trees. However, there are no summarizing papers on this topic now which is one of the most understudied. The author has collected new folklore materials on this topic in Tevrizsky district of Omsk region in 2011-2015s. The article is devoted to the worship of trees by the Tatars from the north part of Omsk region. The religious and ceremonial complex as well as sacral-mythological content are analyzed, also there is given its comparison with the cults of the Volga Tatars and their neighboring aboriginal population, the transformation of the cult elements under the influence of Islam is showing. Author also highlights beliefs about the characters and images of traditional Tatar mythology that associated with trees: the forest owner, Ayesha Fatima. The folklore materials can be nominally divided into several groups: veneration of forest (forbidden territory that is guarded by a spirit), revered groves (sacralization of some particular groves), revered trees (religious animation of a tree, worship of individual species of tree). Рассмотрены работы по исследованию почитания деревьев сибирскими татарами.